DETERMINANTS OF CUSTOMER SATISFACTION AND LOYALTY IN THE NIGERIAN TELECOMMUNICATIONS INDUSTRY - Oghojafor; Akpoyomare, B.E.; Ladipo; Patrick, K.A.; Ighomereho; Salome, O.; Odunewu; Victor, A. (British Journal of Marketing Studies, 2014)
Customer satisfaction and loyalty have been identified as critical success factors in any business organization. Recent developments in the Nigerian telecommunications industry indicate that the operators engage in several marketing activities to ensure that their subscribers are satisfied and brand loyal. However, most subscribers complain about the quality of services and some switch from one operator to the other or use several lines. Consequently, this paper examined the marketing activities that influence customer satisfaction and the factors that determine customer loyalty in the industry. Based on a contemporary definition of marketing, five constructs (product, price, distribution, promotion and customer service) were identified and tested. For the purpose of the study, a sample size of one thousand (1000) respondents was selected from Lagos State, Nigeria through purposive sampling technique and data were obtained employing a structured close-ended questionnaire. The results revealed that product (core service), promotion and distribution have a higher impact on the level of customer satisfaction. It was also found that, apart from customer satisfaction, trust is a major determinant of customer loyalty in the telecoms market. On the bases of these findings, a number of recommendations for telecom operators and the Nigerian government were outlined.